Pemanfaatan Tanaman Pangi (Pangium Edule Reinw) pada Lahan Agroforestri Desa Watu Toa Kecamatan Marioriwawo Kabupaten Soppeng - Munawwarah Nawir; Ira Taskirawati; Baharuddin Baharuddin (Fakultas Kehutanan, Universitas Hasanuddin, 2017)
Pangi (Pangium edule Reinw) is a type of commodity of Non-Timber Forest Product group, which all parts of this plant can be utilized. Pangi crops grown on agroforestry land is one of the preservation of this plant in order to be utilized sustainably. To fulfill the necessities of life, the people of Desa Watu Toa manage their land by making it as an agroforestry land and planting seasonal crops, fruits and forestry crops. One type of forest crops planted is Pangi. This study aims to identify the utilization of pangi by the community in Watu Toa Village, Marioriwawo District, Soppeng District. Survey (direct observation and questioner) and interview are the methods used in this research. The data obtained are arranged in table form and described in descriptions to describe the utilization of pangi by farmers in Watu Toa Village, Marioriwawo Subdistrict, Soppeng Regency. There are four hamlets in the village of Watu Toa, but this research is only conducted on Dusun Masumpu and Dusun Jampu-jampu. In both villages, there is a pangi plant on agroforestry land managed by farmers. The area of agroforestry in both hamlets is on average between 0.25-0.50 ha. Watu Toa Village Farmers only utilizes six products produced from pangi plant, namely construction materials (stems); fish poison (skin); natural pesticides (leaves), antiseptics (leaves), vegetables (young leaves); as well as fruit / pangi as an ingredient that can be cake, tempeh, vegetable ise 'pangi, vegetable Lope' pangi, and cooking spice (kluwak).